Investigation of the joint effect of light pressure and secular resonances associated with the mean motion of the sun on the dynamics of objects in the LEO region - Blinkova, E. V. (Solar system research)
The features of the joint influence of light pressure and secular resonances associated with the average motion of the Sun on the dynamics of low-flying objects are studied. Maps of the distribution of resonances with the average motion of the Sun and maps of the amplitude of eccentricity oscillations are constructed. Real objects are marked on all maps, the position of which is taken from the NORAD catalog. The dynamics of some real objects have been studied. It is shown that light pressure can reveal and enhance the influence of secular resonances, which, in turn, leads to an increase in the amplitude of eccentricity oscillations and chaotization of motion.